Anxiety and depression levels in patients with chronic orofacial pain - Naomi Rahman; Norma O'Connor; Zaid Sadiq; Victor Lopes (Open Journal of Pain Medicine - Peertechz Publications, 2020)
Introduction: Orofacial pain can be highly distressing, affecting 10% of the population and is associated with psychological symptoms. This study aims to assess the frequency of such psychological symptoms in orofacial pain patients compared to a control group and how these symptoms change with treatment. The effect of social deprivation will also be explored.  Method: We conducted a prospective study comparing 342 consecutive referrals to the pain clinic over a nine-year period with 100 controls. Exclusion criteria involved patients with dental/dentoalveolar pain or trigeminal neuralgia. The chronic faical pain patient's data was collected from validated questionnaires completed at every consultation. The somatic diagnoses were based on a interview process with one consultant conducting the pain clinic.  Results : The average age of patients and controls was 49.5 years. There was a statistically significant difference (p = 0.032) between the anxiety and depression scores respectively of patients (average 8.6 & 6) and controls (6 & 2.1). The pre-treatment anxiety scores were statistically significantly higher in improvers compared to non-improvers (p < 0.05) but not with the depression scores.  Conclusion: Forty-two percent of patients reported improvement in their symptoms. A statistically significant correlation was found between anxiety and improvement following treatment, however not in depression scores. It is evident that while pain is managed effectively and anxiety is successfully reduced, depression is not treated. Deprivation is not a confounding factor in the experience of pain, anxiety, depression or improvement in symptoms. Therefore, treatment can be beneficial in reducing anxiety. However, this was not the case for depression scores and improvement following treatment and therefore it is unclear whether there was a psychological health benefit to these patients following treatment.